International legal cooperation of states in the fight against space debris - Dinar A. Valeev, Adel I. Abdullin, (Opción, 2019)
In the current article, the authors consider the problem of debris in the near-Earth space environment, and investigate the legal and technological aspects of this issue. General and special methods of scientific knowledge are applied in the work. Analysis and synthesis are the central research methods. As a result, in the modern system of international law, public international law should create certain rules, aimed at ensuring space security and space order. In conclusion, it is necessary to fight against space debris, using a set of technical and legal mechanisms, applying the joint efforts of the whole international community.